The New Development Politics : the Age of Empire Building and New Social Movements - Petras, James (Ashgate, 2003)
A critique of contemporary conceptions of international political economy, the role of the state and contemporary social movements, The New Development Politics challenges the dominant paradigms in the field of development studies. Raising fundamental theoretical and empirical questions, it provides a coherent response to the increasing militarization of inter-state relations, increasing protectionism and inter-state rivalries and the growing age of state intervention in political, economic and social life. The study presents a critical analysis of US empire-building, the role of dirty money and political power, as opposed to technological change. It features a discussion of neo-mercantilism as a new mode of empire and examines the role of movements of unemployed and landless peasants in key Third World countries.